A novel HLA‐B*18 allele, HLA‐B*18:124, identified in a German volunteer bone marrow donor. (15th November 2016) - Sidahmed, A. M. E.; Mohamed, T.; Stamm, L.; Khan, F.; Berka, N.
Abstract: HLA‐B*18:124 differs from B*18:01:01:02 by a single substitution in exon 4.